LEGAL REVIEW OF THE APPLICATION OF THE SYSTEMATIC LEX SPECIALIS PRINCIPLE IN HANDLING TAX CRIMINAL CASES - Batistuta, Nafathony Setya Mohammad; Purnawan, Amin (UNISSULA Semarang, 2024)
One of the characteristics of the legal principle is dynamic so that it can be adjusted to the development of the times. Likewise, the principle of lex specialis derogat legi generali has undergone theoretical development. One of the derivatives of the principle of lex specialis derogat legi generali is the principle of lex specialis systematic. This study aims to determine the legal review of the application of the principle of lex specialis systematic in handling tax crime cases. In this study, the approach method used is: a normative legal approach by studying library materials. The research specification used is Descriptive Analytical, namely an effort to analyze and explain legal problems related to objects with a comprehensive and systematic description of all matters related to the application of the principle of lex specialis systematic in tax crimes. The concept of implementing the principle of Lex Specialis Systematis is determined by which Special Law is enforced, meaning that special criminal provisions if the legislators do intend to enforce the criminal provisions as special criminal provisions or it will be special from the existing special provisions, then the general taxation provisions law is the one that is enforced, even though other special laws (such as the Corruption Crime Law have elements of a crime that can cover it) are of an acceptability nature. The position of the principle of Lex Specialis Systematis in Law No. 28 of 2007 concerning General Taxation Provisions in Tax Crimes if the dispute is within the scope of tax, then the law on taxation is used.